Hydatidosis of the long bones treated with en bloc resection and reconstruction with mega prosthesis– a report of 2 cases - Khalil Amri; Ramy Triki; Rabie Ayari; Khaled Khelil; Achraf Abdennadher; Mohamed Manai; Haythem ElAskri; Eya Ben Amri (BMC Musculoskeletal Disorders, 2025)
Abstract Introduction Osseous hydatidosis is a rare condition caused by a cestode called Echinococcus Granulosus. The bone invasion is rare and accounts for only 0,5–4% of all forms of hydatidosis. Its treatment is difficult as they are diagnosed late due to the lack of specific symptoms. We describe in this article two cases who had major invasion of long bones. Cases First case is a 45-year-old-woman consulted for recurrent pain in her right shoulder and arm. Plain X-rays seemed normal. CT-scan of the shoulder and humerus revealed cysts invading the proximal humerus. The MRI showed osteolytic and multiloculated images invading the entire right humerus. A surgical biopsy was performed showing hydatid cysts. Surgery was performed with en bloc resection of the whole humerus and replacement by total humeral mega prosthesis. At the last follow-up of 1 year and a half, patient had no local or general recurrence of the disease with satisfactory function of the right upper limb.Our second patient is a 39-year-old woman. She consulted for recurrent right hip pain and limping. Plain X-rays showed an aggressive osteolytic image involving major part of the proximal femur with a diaphyseal extension. MRI showed multiple cysts lesions involving major parts of the femur. Surgical biopsy was performed, and microscopic findings were in favor of hydatid cyst. Total en bloc resection of the right femur was performed. Replacement was done by a total femoral mega prosthesis. At the last follow-up of five years post operatively, patient was walking pain free with good function of right lower limb, without any recurrence. Conclusion Osseous hydatidosis is a slow evolving and difficult to treat disease once involving a whole large bone. It must be treated as malignant tumor. In fact, they can be locally aggressive and have high level of recurrence. En bloc resection followed by total replacement of the large affected bone by a mega prosthesis seems to be a promising technique.